Pengaruh Strategi Pemasaran, Kebijakan Pemerintah, Dan Kinerja Karyawan Terhadap Peningkatan Profitabilitas Perusahaan Dengan Volume Penjualan Sebagai Variabel Intervening di PT ANTAM Tbk UBPP Logam Mulia - Rachmanti, Arum; Sudigdo, Agus (Journal of Economics and Business UBS, 2025)
PT ANTAM Tbk UBPP Logam Mulia is one of the leading precious metal producers and traders in Indonesia. Despite the fluctuations in world gold prices, the company was still able to record an increase in sales volume. This study aims to analyze the influence of marketing strategies, government policies, and employee performance on company profitability, with sales volume acting as a mediating variable. The quantitative method was used with a Structural Equation Modeling approach based on Partial Least Squares (SEM–PLS) using SmartPLS, involving 90 internal respondents as well as secondary data as support. The research instrument has met the validity and reliability requirements, with AVE values ≥ 0.5, Composite Reliability ≥ 0.7, and HTMT < 0.90. The results show that marketing strategies, government policies, and employee performance have a positive and significant influence on sales volume, but do not have a direct effect on profitability. Sales volume has been shown to mediate the relationship between these three variables and profitability significantly, indicating that increased profitability can only be achieved if marketing strategies, government policy support, and employee performance succeed in increasing sales volume. These findings provide practical implications for the management of PT ANTAM Tbk UBPP Logam Mulia to focus on strengthening marketing strategies, optimally utilizing government policies, and improving employee competencies to drive sales, which ultimately increases the company's profitability in a sustainable manner.